(untitled) (American Journal of Management, 2024)
This case study explores innovative approaches to expand access to high-quality internships and improve equitable student outcomes. It focuses on Lehigh University’s virtual Innovation Internship program, partnered with the Nasdaq Entrepreneurial Center and Epixego Inc. The program aims to address challenges in traditional internships, such as hidden curriculum, false narratives, and unequal social environments. By incorporating self-assessment of learning competencies and enhancing student agency, the program doubled its capacity to 40 students. The study measured student self-efficacy, occupational identity choice, and outcome expectations based on various factors. Results showed that students changed internship preferences across occupation categories and experienced increases in entrepreneurial self-efficacy (3%), occupational identity (7%), and perception of entrepreneurship education (4%). This multifaceted approach demonstrates the potential for innovative internship designs to improve accessibility and student development outcomes.